2017
DOI: 10.1155/2017/6748948
|View full text |Cite
|
Sign up to set email alerts
|

A Prototypical First-Generation Electronic Cigarette Does Not Reduce Reports of Tobacco Urges or Withdrawal Symptoms among Cigarette Smokers

Abstract: It is unknown whether first-generation electronic cigarettes reduce smoking urges and withdrawal symptoms following a 24 h deprivation period. This study tested whether a first-generation electronic cigarette reduces smoking urges and withdrawal symptoms in cigarette smokers. Following 24 h of tobacco deprivation, using a within-subjects design, eight nontreatment seeking tobacco cigarette smokers (3 females) administered 10 puffs from a conventional cigarette or a first-generation electronic cigarette contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although smoking is changing from traditional tobacco cigarettes to electronic cigarettes worldwide, only 0.9% of the adults in China smoked electronic cigarettes in 2018 . Some studies have shown that smoking urges and withdrawal symptoms in cigarette smokers are not reduced by using e-cigarette. , The popularity of e-cigarettes may lead to an increase in smoking rates among adolescents, and there is evidence that adolescents who use e-cigarettes are more likely to smoke tobacco products than nonusers. , Therefore, we think it is reasonable to apply the present smoking emissions for the simulation, considering the negligible proportion of electronic cigarette smokers. Second, our estimation of deaths and economic losses when outdoor air meets WHO AQG 2021 was based on the population, age structure, death rate due to diseases, and per capita disposable income in 2019, which has some influence on the results.…”
Section: Discussionmentioning
confidence: 99%
“…Although smoking is changing from traditional tobacco cigarettes to electronic cigarettes worldwide, only 0.9% of the adults in China smoked electronic cigarettes in 2018 . Some studies have shown that smoking urges and withdrawal symptoms in cigarette smokers are not reduced by using e-cigarette. , The popularity of e-cigarettes may lead to an increase in smoking rates among adolescents, and there is evidence that adolescents who use e-cigarettes are more likely to smoke tobacco products than nonusers. , Therefore, we think it is reasonable to apply the present smoking emissions for the simulation, considering the negligible proportion of electronic cigarette smokers. Second, our estimation of deaths and economic losses when outdoor air meets WHO AQG 2021 was based on the population, age structure, death rate due to diseases, and per capita disposable income in 2019, which has some influence on the results.…”
Section: Discussionmentioning
confidence: 99%